SINTESIS GRAPHENE OXIDE DAN REDUCED GRAPHENE OXIDE - Yeti Rafitasari; Haris Suhendar; Nurul Imani; Fitri Luciana; Hesti Radean; Iman Santoso (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Graphene oxide (GO) and reduced graphene oxide (rGO) have been synthesized chemically from graphite powder. Graphite powder was oxidized with strong oxidator agent molekul  to get graphite oxide, this process was called by Hummerâ€™s methode. Graphite oxide was dispersed in water with ultasonic vibrator to exfoliated graphite oxide layers, and become graphene oxide. Epoxy group in GO structure was reduced by hydrazine 80 wt% to get rGO. Comparation was done between self synthetic rGO and Sigma Aldrich synthetic rGO using UV-Vis and FTIR spectroscopy, which showed that optical properties of self synthetic rGO have same UV-Vis and FTIR spectroscopy with Sigma Aldrich synthetic rGO.Keywords: Graphene Oxide, Reduced Graphene Oxide, Sigma Aldrich, Optical Properties.